Calibration and Methodology of Commercial Solid-Phase Microextraction Preconcentration and Ultraviolet Absorption Spectroscopy for Determination of Aromatic Compound in Water - Abu-Shammla, Farida (Asian Journal of Chemistry, 2012)
A new solid-phase microextraction (SPME) procedure extracts aromatic compounds in water at part-billion concentrations from aqueous samples using a small disk of poly (dimethel) siloxane) (PDMS) and ultraviolet absorption spectroscopy. The reversed-phase disk (PDMS) removes nonpola aromatic compounds from contaminated water at equilibrium time measured using standards from each aromatic compound studied. It was found that equilibrium is established in the range of 40-60 min, with the exception of naphthalence and 1-methyl naphthalance, equilibrated within 90 and 100 min, respectively. After the equilibrium is established the concentration of aromatic hydrocarbon in the sorbent disk is determined quantitatively by UV absorption spectra at 260 nm. The detection limit of the procedure was ranging from 0.5 to 10 prob. Relative standard deviation from the complete procedure was ranging from 3 to 12%.